Обладнання для вирощування рослинних клітин глибинними способом - Пенчук, Юрій Миколайович; Лич (Ткаченко), Інна Валентинівна; Мороз, Ольга Сергіївна; Соколовський, О. С.; Коломієць, Юлія Василівна (My University, 2012)
В роботі зроблено аналіз існуючих систем, які використовуються при культивуванні рослинних клітин для подальшого використання в технології одержання біологічно активних речовин та при великомасштабному мікроклональному розмноження рослин. Вибрано основні базові моделі для розроблення та конструювання біореактора, який в подальшому буде використано для культивування клітин рослин. The analysis of the existing systems, used for cultivation of vegetative cells for the further use in technology of biologically active substances obtaining and at large-scale microclonal reproduction of plants is presented. The primary base models for working out and designing the bioreactor for the future use for cultivation of vegetative cells were chosen. Constructed apparatus is equipped with a mixing device as Archimedes screw that allows to mix the culture broth gently. In addition, this type of stirrer generates a directed flow, maintaining cells in suspension. Aeration is carried out through a bubbler, which is a porous glass membrane. A diffuser for additional distribution of oxygen in to the cultural broth is located in the middle of the apparatus.
Keywords: біореактор; калюсна культура; bioreactor; cell culture; кафедра біотехнології і мікробіології